Service Quality in Granting Licensing and Recommendations in the Field of National Unity and Politics at the Kesbangpol Office Bolaang Regency, North Mongondow - Wilda Mangula; Widya Kurniati Mohi; Lukfiah I Radjak (Journal of Management and Administration Provision, 2021)
The research was based on the formulation of the quality service in giving of license and recommendations in the Office of National Unity and politics North of Bolaang Mongondow. As for the main purposes of this research was to know the quality service in giving license and recommendation in the Office of National Unity and Politics North of Bolaang Mongondow. The method used in this research is qualitative with phenomenological approach. The data collection is done by observation interviews and documentation and data analysis is descriptive, then checking the validity of the data. The result showed that the quality service in giving of license and recommendations in the Office of national Unity and Politics North of Bolaang Mongondow, in therms of quality quantity timeliness, effectiveness, independence, commitment to work im general, that is good so it needs the improvement of human resources in order facilitate achievement of the organization’s vision and mission.